Keragaman Genetik dan Karakter Agronomi Galur-galur Kacang Bogor (Vigna subterranea L. Verdc.) Hasil Seleksi Galur Murni Asal Lanras Sukabumi - Memen Surahman; Arifah Rahayu; Yuliawati; Yudiwanti Wahyu (JURNAL AGRONIDA, 2018)
Bambara groundnut is a legume plant that has several advantages, including droughttolerance, has ability to grow on infertile land and high nutrient content. The production ofbambara groundnut is still low, so it is necessary to obtain high yielding bambara groundnut line.The experiment was conducted to evaluate the genetical variation and agronomic characters of 30bambara groundnut lines. This experiment was carried out in experimental field of SEAMEOBIOTROP Tajur Bogor (± 280 m above sea level), on Februari-June 2018. Plant materials used inthis research were 30 bambara groundnut lines derived from pure line selection of Sukabumilandrace and unselected Sukabumi landrace uses as control. The experiment was arranged in arandomized complete block design with three replications. Results showed that there werevariations among several agronomic characters of bambara groundnut lines. Several lines showedsuperior characters. R59.30, A90.8, A41.4, A56.10, A43.5, A103.5, A41.4, A55.8, R59.31 andA28.10 lines were lines with the higest dry pods weight compared to the other lines and controlline. These lines had potential as new superior varieties of bambara groundnut.Keywords: landrace, new superior variety, pure line selection